CURRENT LEVEL OF INVESTMENT POLICY AND STATE ENCOURAGEMENT IN THE MARKET OF FRUIT AND VEGETABLE PRODUCTS OF UZBEKISTAN - Kurbonov Jasurbek Pozilovich (Research Parks Publishers, 2023)
This in the article in Uzbekistan fruits and vegetables products to the market foreign investments attraction to do about done being increased to reforms about issues statement done